2022
DOI: 10.1111/srt.13158
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of dermoscopy and reflectance confocal microscopy accuracy for the diagnosis of psoriasis and lichen planus

Abstract: Background: Dermoscopy and reflectance confocal microscopy (RCM) as noninvasive tools are gaining increasing importance in the diagnosis of inflammatory skin disorders.The purpose of our study was to calculate and compare the diagnostic accuracy of dermoscopy and RCM in common inflammatory skin diseases. Materials and Methods:We retrospectively collected clinical, dermoscopic, and RCM images of psoriasis and lichen planuscases from March 2018 to February 2021 in China-Japan Friendship Hospital. There were 10 e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 29 publications
0
3
0
2
Order By: Relevance
“…As regards dermoscopy, it is a noninvasive tool which allows to increase the accuracy of the diagnosis of psoriasis. 43 Generally, dermoscopic examination of plaque psoriasis shows a distinctive pattern characterized by diffuse white scales and regularly and symmetrically distributed dotted vessels on a light or dull red background. 44 , 45 In our study, we reported that dermoscopic examination may be used not only during the diagnosis but also for assessing the severity of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…As regards dermoscopy, it is a noninvasive tool which allows to increase the accuracy of the diagnosis of psoriasis. 43 Generally, dermoscopic examination of plaque psoriasis shows a distinctive pattern characterized by diffuse white scales and regularly and symmetrically distributed dotted vessels on a light or dull red background. 44 , 45 In our study, we reported that dermoscopic examination may be used not only during the diagnosis but also for assessing the severity of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…Studies conducted so far have not shown the presence of WS in diseases other than lichen planus [8], and Wang et al [19] found that WS and bluegray dots found in dermoscopy in 65.3% and 61% of 47 patients diagnosed with lichen planus, respectively, are reliable criteria in the differential diagnosis of lichen planus from other dermatoses associated with scaling [18,19]. WS is a marker of the active phase of lichen planus and is used to assess the effectiveness of treatment, as it disappears in course of a properly selected therapy [18].…”
Section: Lichen Planusmentioning
confidence: 91%
“…liszaj płaski [8], a ponadto Wang i wsp. [19] na podstawie przeprowadzonego badania stwierdzili, że siateczka Wickhama i niebiesko-szare kropki występujące w badaniu dermoskopowym odpowiednio u 65,3% i 61% wśród 47 pacjentów ze zdiagnozowanym liszajem płaskim. Zmiany te stanowią wiarygodne kryteria w diagnostyce różnicowej liszaja płaskiego z innymi dermatozami [18,19].…”
Section: Liszaj Płaskiunclassified
See 1 more Smart Citation
“…Currently, the diagnosis of psoriasis is mainly based on the patient's typical clinical manifestations, dermoscopy, and skin biopsy 8,9 . Histopathological examination is an invasive method and has not become routine test for psoriasis.…”
Section: Introductionmentioning
confidence: 99%